(untitled) (Panacea Journal of Medical Sciences, 2025)
Introduction: Less than 1% of all malignancies and 3-5.5% of all head and neck tumors are salivary gland neoplasms. Salivary gland tumors occur in 0.4 to 13.5 instances per 1 lakh people worldwide each year. Salivary gland neoplasms include a wide range of benign and malignant tumors. Aim and Objective: This study aims to categorize different salivary gland tumours in accordance with WHO classification and to examine the frequency of salivary gland lesions with relation to age, sex, and location of lesion. Materials and Methods: Salivary gland soecimens were delivaered to the histopathology section in 10% formalin. They were carefully labelled, fixed and meticulously prepared for gross examination. Sections were taken from the lesion, margins, surrounding tissue and lymph nodes if any. 3-5 micrometer serially cut paraffin wax sections were processed. Hematoxylin and eosin (H&E) stained slides were examined and findings were documented. The acquired data underwent analysis and tabulation utilizing SPSS software. Results: 64 specimens of salivary gland lesions were studied in the present study. The age range of these patients varied from 13 years to 76 years. Benign cases formed the bulk of this study (54.69%) followed by non- neoplastic and malignant cases. Benign tumors were predominantly noted in the neoplastic lesions studied accounting for 72.92% cases followed by malignant tumors 27.08%. Pleomorphic adenoma was the only benign neoplasm encountered in our study. Conclusion: The most predominant malignant neoplasm was mucoepidermoid carcinoma. Adenoid cystic carcinoma, Secretory carcinoma, Clear cell carcinoma and Polymorphous adenocarcinoma were also reported.